Modeling Mercury Contamination In The Evreglades Ecosystem : From Atmospheric Transport To Wetland. - Shamlan, Munir; Koh, Hock Lye; Gooi, Bee Seung; Lee, Hooi Ling; DeAngelis, Donald; Teh, Su Yean (2005)
The Florida Everglades is a vast wetland of about 10,000km located in Southern Floridaof The United States Of America.Bioaccumulation of mercury in the aquatic food chain in the Florida Everglades has been concert for seversl decades.High mercury burdens of 2.5mg/kg have been recorded by the Florida Department of Health in the largemouth bass in the Everglades,a level that is deemed unsafe by all health-based standards.The major sources of mecury in the Everglades wetlands are deprived from industrial combustions and waste incinerations transportedthrough the atmosphere over different lenght scales.